Genetic markers of One-Carbon Metabolism Disorders in Schizophrenial - T. V. Zhilyaeva; A. S. Piatoikina; A. S. Blagonravova; G. E. Mazo (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The paper presents the results of the literature review and the authors’ own studies of the association of several several single-nucleotide genetic polymorphisms (SNP), which affect one-carbon metabolism, with a risk of schizophrenia and the severity of some clusters of its symptoms. Directions for further study of the role of a number of SNP of enzymes in the folate metabolism cycle and related biochemical processes in schizophrenia (in particular, their influence on the effect of personalized correction of one-carbon metabolism disorders) are determined.